2021
DOI: 10.1089/heq.2020.0081
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Measures of Structural Racism into Population Studies of Reproductive Health in the United States: A Narrative Review

Abstract: Purpose: Black women in the United States face poor outcomes across reproductive health measures—from pregnancy outcomes to gynecologic cancers. Racial health inequities are attributable to systemic racism, but few population studies of reproductive health outcomes integrate upstream measures of systemic racism, and those who do are limited to maternal and infant health outcomes. Advances in understanding and intervening on the pathway from racism to reproductive health outcomes are limited by a pau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(59 citation statements)
references
References 100 publications
1
57
0
1
Order By: Relevance
“…Our findings resonate strongly with those of other reviews on this topic which have reported similar connections between racialized segregation a broad range of health outcomes, including vascular diseases, cancer, pregnancy and birth complications, cancer, and lifestyle [9,10,[48][49][50][51]. The present paper, however, advances current knowledge by highlighting poverty as a key pathway through which segregation produces negative health outcomes in racial and ethnic minority populations.…”
Section: Plos Onesupporting
confidence: 91%
“…Our findings resonate strongly with those of other reviews on this topic which have reported similar connections between racialized segregation a broad range of health outcomes, including vascular diseases, cancer, pregnancy and birth complications, cancer, and lifestyle [9,10,[48][49][50][51]. The present paper, however, advances current knowledge by highlighting poverty as a key pathway through which segregation produces negative health outcomes in racial and ethnic minority populations.…”
Section: Plos Onesupporting
confidence: 91%
“…61 Alson and colleagues and Chambers and colleagues have offered potential measures of structural racism that may be incorporated into OBGYN research, including but not limited to legislation and policies, access to care, discrimination, deprivation, geography and place, opportunities, and financial stability. 61,62…”
Section: Adopt a Race-conscious And Multidisciplinary Approachmentioning
confidence: 99%
“…Researchers who include race in their studies to elucidate health inequities should also consider incorporating measures of structural racism into their study design, and seek the expertise of researchers from other fields who have interrogated these ideas for decades 61. Alson and colleagues and Chambers and colleagues have offered potential measures of structural racism that may be incorporated into OBGYN research, including but not limited to legislation and policies, access to care, discrimination, deprivation, geography and place, opportunities, and financial stability 61,62…”
Section: Considerations For Using Race In Future Obgyn Researchmentioning
confidence: 99%
“…[3][4][5][6] In the past decade, scholars and policymakers have increasingly sought to understand the upstream (systemic and structural) factors that have contributed to the disproportionate risk Black pregnant people experience during pregnancy and childbirth. 7 Structural racism-carefully designed "macro-level systems, social forces, institutions, ideologies, and processes that interact with one another to generate and reinforce inequities among racial and ethnic groups" 8 that are present in all facets of our lives-has been identified as a critical determinant of adverse birth outcomes for Black pregnant people. 7 Historically, as a fundamental cause of health inequities, 9 structural racism is not only killing Black men and women; it is also killing their infants.…”
Section: Introductionmentioning
confidence: 99%